Gene expression in breast and adipose tissue after 12 months of weight loss and vitamin D supplementation in postmenopausal women - Caitlin Mason (Nature Portfolio, 2017)
Vitamin D: Supplementation offers glimmer of benefit Vitamin D supplementation may help lower the expression of a cancer-associated gene in breast tissue, according to a preliminary trial. Anne McTiernan, Larissa Korde and colleagues at the Fred Hutchinson Cancer Research Center in Seattle, Washington, USA, ran a 12-month randomized clinical study in which 79 overweight postmenopausal women received either daily vitamin D pills or a placebo while concurrently completing a behavioral weight loss program. At the end of the year-long trial, vitamin D seemed to have no effect on the expression of five cancer-linked genes in either breast or fat tissues compared to placebo. However, women taking the vitamin supplements whose vitamin D levels went up showed a significant drop in their breast tissue in the expression of one cancer-related gene compared to women whose vitamin levels didn’t rise despite the daily pills.